2017
DOI: 10.1016/j.icarus.2016.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing and in situ mineralogic survey of the Chilean salars: An analog to Mars evaporate deposits?

Abstract: The identification and characterization of hydrated minerals within ancient aqueous environments on Mars are high priorities for determining the past habitability of the planet. Few studies, however, have focused on characterizing the entire mineral assemblage, even though it could aide our understanding of past environments. In this study we use both spaceborne and field (VNIR spectroscopy) analyses to study the mineralogy of various salt flats (salars) of the northern region of Chile as an analog for Martian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 85 publications
3
25
0
Order By: Relevance
“…as those that are found in the salars of the Atacama Desert and may have formed via comparable processes (Sutter et al, 2007;Flahaut et al, 2017). The western section of the Atacama Desert lies over a sedimentary bedrock, the Andean section to the East, which encompasses our sampling area, and it is made of a variety of basaltic to dacitic volcanic rocks that may be similar to rocks of the martian crust (Flahaut et al, 2017).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…as those that are found in the salars of the Atacama Desert and may have formed via comparable processes (Sutter et al, 2007;Flahaut et al, 2017). The western section of the Atacama Desert lies over a sedimentary bedrock, the Andean section to the East, which encompasses our sampling area, and it is made of a variety of basaltic to dacitic volcanic rocks that may be similar to rocks of the martian crust (Flahaut et al, 2017).…”
Section: Introductionmentioning
confidence: 92%
“…Common salts/evaporites found in the Atacama Desert include halite, gypsum, anhydrite, borates, sodium sulfates, and perchlorate salts (Stoertz and Ericksen, 1974;Ericksen, 1981;Böhlke et al, 1997;Flahaut et al, 2017). The Atacama Desert has an average temperature of 11-16°C with strong fluctuations during day or night, and with elevation (Stoertz and Ericksen, 1974;McKay et al, 2003;Clarke, 2006;Gómez-Silva et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas hyperspectral remote sensing allows for improved discrimination of the crust mineralogy, which is recommended for complex evaporite mineral assemblages [36], it currently lacks the temporal resolution needed for the analyses and monitoring of the highly dynamic processes of salt pan environments. Some studies demonstrated that it is possible to derive a number of useful mineralogical crust types (e.g., gypsum, carbonate, quartz, and halite) for the classification of playa surface, even with broadband multispectral data, e.g., from Landsat 7 Enhanced Thematic Mapper (ETM+) [37,38] or Landsat 8 Operational Land Imager (OLI) sensor [39]. Nevertheless, a direct mineralogical characterization is not possible.…”
Section: Introductionmentioning
confidence: 99%